Significance of a Posttranslational Modification of the PilA Protein of Geobacter sulfurreducens for Surface Attachment, Biofilm Formation, and Growth on Insoluble Extracellular Electron Acceptors - Richter, Lubna V.; Franks, Ashley E.; Weis, Robert M.; Sandler, Steven J. (Journal of bacteriology, 2017)
Geobacter sulfurreducens , an anaerobic metal-reducing bacterium, possesses type IV pili. These pili are intrinsic structural elements in biofilm formation and, together with a number of c -type cytochromes, are thought to serve as conductive nanowires enabling long-range electron transfer (ET) to metal oxides and graphite anodes. Here, we report that a posttranslational modification of a nonconserved amino acid residue within the PilA protein, the structural subunit of the type IV pili, is crucial for growth on insoluble extracellular electron acceptors. Matrix-assisted laser desorption ionization (MALDI) mass spectrometry of the secreted PilA protein revealed a posttranslational modification of tyrosine-32 with a moiety of a mass consistent with a glycerophosphate group. Mutating this tyrosine into a phenylalanine inhibited cell growth with Fe(III) oxides as the sole electron acceptor. In addition, this amino acid substitution severely diminished biofilm formation on graphite surfaces and impaired current output in microbial fuel cells. These results demonstrate that the capability to attach to insoluble electron acceptors plays a crucial role for the cells' ability to utilize them. The work suggests that glycerophosphate modification of Y32 is a key factor contributing to the surface charge of type IV pili, influencing the adhesion of Geobacter to specific surfaces. IMPORTANCE Type IV pili are bacterial appendages that function in cell adhesion, virulence, twitching motility, and long-range electron transfer (ET) from bacterial cells to insoluble extracellular electron acceptors. The mechanism and role of type IV pili for ET in Geobacter sulfurreducens is still a subject of research. In this study, we identified a posttranslational modification of the major G. sulfurreducens type IV pilin, suggested to be a glycerophosphate moiety. We show that a mutant in which the glycerophosphate-modified tyrosine-32 is replaced with a phenylalanine has reduced abilities for ET and biofilm formation compared with those of the wild type. The results show the importance of the glycerophosphate-modified tyrosine for surface attachment and electron transfer in electrode- or Fe(III)-respiring G. sulfurreducens cells.